Synthesis of Glycosylated Natural Products - Huang, Gangliang; Zhang, Xueqin; Li, Min; Li, Ping; Luo, Deqi; Liu, Zhangmei (Current Organic Synthesis, 2014)
Many efforts have been made for developing novel and efficient methods to synthesize the glycosylated natural products. This review summed up recent advances on the synthesis of glycosylated natural products.
Keywords: recent advances